Pengaruh Strategi Tax Planning dan Manajemen Laba terhadap Persistensi Laba: Studi Empiris Perusahaan Sektor Barang Konsumsi Primer Terdaftar di Bursa Efek Indonesia - Raihan Nur Ihsan; Nurzi Sebrina (Jurnal Eksplorasi Akuntansi, 2026)
This study investigates the impact of aggressive tax planning and aggressive earnings management on earnings persistence. Using purposive sampling, 252 firm-year observations of primary comsumption sector companies listed on the Indonesia IDX from 2021 to 2023 were analyzed. The results show that aggressive tax planning lower level of earnings persistence than other companies (All-Other Firms) and earnings management actually show a higher level of earnings persistence than other companies (All-Other Firms).